Sustainability, Spread, and Shift: Developing a Professional Learning Program for Out-of-School Educators With Scale-Up in Mind - Peterman, Karen; Robertson Evia, Jane; Allen, Sue; Byrd, Scott C.; Nickerson, Brittney; Kastelein, Kate (Frontiers in Education, 2021)
This case study describes the iterative process used to develop a virtual coaching program for out-of-school-time (OST) educators, particularly those who work in afterschool and library settings. The program, called ACRES (Afterschool Coaching for Reflective Educators in STEM), used a design-based implementation research (DBIR) approach to consider issues related to scale-up. Afterschool and library settings are complex systems that include supports and barriers that require adaptation for implementation. Throughout the design process, program developers worked to identify the essential elements of the program that should be maintained across contexts, while attending to the diverse needs of individual OST settings. Survey and interview data were collected from the full range of stakeholders throughout the implementation process to verify the importance of the essential elements to the professional learning model, and to gather early indicators of the program’s potential related to three key concepts for successful scale-up of programs: sustainability, spread, and shift. Conclusions are shared in relation to how these types of results support the scale-up of programs, and the strengths and gaps in the process used to apply the DBIR approach in our work.